Biodiesel production from Calophyllum inophyllum−palm mixed oil. Issue 12 (18th June 2017) - Damanik, Natalina; Ong, Hwai Chyuan; Chong, W.T.; Silitonga, A.S.
ABSTRACT: The objective of this study is to investigate the biodiesel production from Calophyllum inophyllum −palm mixed oil. The C. inophyllum –palm biodiesel ( C. inophyllum palm oil methyl ester, CPME) is first produced by mixing the crude oils at an equal ratio of 50:50 vol%, followed by degumming, acid-catalyzed esterification, purification, and, last, alkaline-catalyzed transesterification. With this systematic procedure, the acid value of the CPME is 0.4 mg KOH/g, resulting in a significant enhancement of oxidation stability (114.21 h). The results indicate that the fatty acid methyl ester composition of the CPME may be the reason for its larger higher heating value (39.4 MJ/kg) and lower kinematic viscosity (4.15 mm 2 /s). In short, CPME satisfied the ASTM D6751 and EN 14214 standards as a promising alternative fuel in the future.